2023
DOI: 10.1051/0004-6361/202245415
|View full text |Cite
|
Sign up to set email alerts
|

Flybys in debris disk systems withGaiaeDR3

Abstract: Context. Debris disks represent the last phase of the evolution of protoplanetary disks around young stellar objects where planetary systems had most likely already been formed. Resolved systems show peculiar structures, such as asymmetries or spirals, which may be associated with either the presence of a low-mass companion or dynamical interactions with a perturber during a flyby event.Aims. We aim to observationally and statistically constrain the influence of flybys in the formation and evolution of debris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…As discussed in Picogna & Marzari (2014), misalignments are considered to be a particular signature of a past flyby, with a maximum tilting value of 9°, while multiple flybys can lead to higher misalignments. However, after reconstructing the flybys of debris disks using the Gaia Early Data Release 3 data, Bertini et al (2023) found that AU Mic did not experience any flyby in the last 5 Myr, so any misalignment induced by a recent close flyby appears unlikely. It is also important to point out that if a flyby had occurred, we would expect to see both AU Mic b and c become highly misaligned along with AU Mic d. Moreover, most of the Kepler compact multiplanet systems are well-aligned with a scatter of ± 3° (Lissauer et al 2011;Fang & Margot 2012;Fabrycky et al 2014).…”
Section: Coplanarity Of the Au Mic Systemmentioning
confidence: 99%
“…As discussed in Picogna & Marzari (2014), misalignments are considered to be a particular signature of a past flyby, with a maximum tilting value of 9°, while multiple flybys can lead to higher misalignments. However, after reconstructing the flybys of debris disks using the Gaia Early Data Release 3 data, Bertini et al (2023) found that AU Mic did not experience any flyby in the last 5 Myr, so any misalignment induced by a recent close flyby appears unlikely. It is also important to point out that if a flyby had occurred, we would expect to see both AU Mic b and c become highly misaligned along with AU Mic d. Moreover, most of the Kepler compact multiplanet systems are well-aligned with a scatter of ± 3° (Lissauer et al 2011;Fang & Margot 2012;Fabrycky et al 2014).…”
Section: Coplanarity Of the Au Mic Systemmentioning
confidence: 99%